PROBABILISTIC-STATISTICAL MODEL OF CHILDREN'S HEALTH - S.M. Chechel'nitskaya; A.A. Mikheeva; I.S. Kolemasov; M.V. Timakova; V.T. Finagin; A.G. Rumyantsev ("Paediatrician" Publishers LLC, 2009)
The article continues the series of publications on development of informational system of interdisciplinary monitoring of children's and adolescents' health. The results of factor analysis, obtained during examination of more than 10,000 schoolchildren of 1-11 forms living in Moscow, Vologda, Nalchik, Reutov, Petropavlovsk-Kamchatskiy cities are described in this article. Authors formed the list of factors, which allow classification of child's health from the anthropological positions: physical development, functional state, development of personality, and characterizing the social environment of child's education. The probabilistic-statistical model of health was developed on the base of linear conversion of indices (numerical expression of factor). The article show 2 forms of data visualization, facilitating the information perception and allowing the making of relative analysis of health rates (on discoordination, density, dispersion).Key words: children, health, informational systems.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(4):10-16)